Assembly and peptide binding of major histocompatibility complex class II heterodimers in an in vitro translation system. - Hedley, M L (1994)
In vitro transcription/translation of HLA-DR1 cDNAs in the presence of microsomal membranes was used to study the association of major histocompatibility complex class II molecules with peptide and invariant chain (Ii) in the endoplasmic reticulum (ER). HLA-DR alpha and HLA-DR beta subunits assembled into SDS-unstable heterodimers in the absence of exogenous peptide. The inclusion of synthetic peptides during the alpha/beta assembly process promoted their conversion to SDS-resistant heterodimers. Addition of Ii RNA during the translation of HLA-DR alpha and HLA-DR beta RNAs resulted in the formation of alpha/beta/Ii complexes. Peptide binding by class II molecules was detected even when excess Ii was present during alpha/beta assembly. These findings indicate that peptides can bind alpha/beta heterodimers in the ER microenvironment and suggest that peptides derived from cytosolic proteins that are presented by class II molecules at the cell surface may have bound to HLA-DR in the ER.